STATUS OF SCIENCE TEACHING IN INDIAN SCHOOLS FOR THE VISUALLY IMPAIRED CHILDREN - Gupta, H.O.; Singh, Anupama (SCHOOL SCIENCE, 2013)
Education for all by 2000, including disabled children, is a global commitment. In this basic education, science education also has an important role to play. The teaching of science at the foundation stage of schooling deserves utmost care. But it is often given a low priority in special education. The disabled children also have a great need, like anyone else, to learn about the world around them where scientific and technological advancement affect everybody’s life. Science can be used as a motivation to stimulate learning in a number of different academic and social areas and even to provide a basis for vocational education leading to employment opportunities in the modern technologically advanced environment.